Indicadores de performance na cadeia de suprimentos - Gennaro, André Assumpção de (2004)
This dissertation try to explore, using the concept of Supply Chain as a set of activities related to the management of the materiais flow and Logistic Management, not only the importance of the correlated processes as: planning, implementation and control of the materiais flow, but also, the importance to measure and to monitor the performance of these processes, as a practical form to keep the company competitive and actual in íts practíces. This study shows some concepts on key performance indicators, its functions, implications and applicability, in order not to be misinterpreted or misused, once nowadays the superiority of the companies depends on the correct interpretation and use of performance indicators. For many firms, the service differentiation is accomplished by how well the logistics process is managed. To reach excellency in logistics, it must be assured that the key logistics processes are aligned with the firm's central business strategy and measured against predetermined performance objectives. Additionally, firms are jointly defining the specifics of each measure with their trading partners (customers I suppliers I subcontractors) in order to create a common agreement of expectations and results.